Slightly-deformed clouds of enhanced mesospheric sodium and potassium concentration over the SAMA region: a case study - Santos, A. M.; Yang, G.; Pimenta, A. A.; Andrioli, V. F.; Batista, P. P.; Brum, C. G. M.; Resende, L. C. A.; Chagas, R. A. J.; Batista, I. S.; da Silva, L. A.; Moro, J.; Martins, M. P. P.; et al. (Frontiers in Astronomy and Space Sciences, 2025)
This work investigates a slightly-deformed cloud of enhanced mesospheric sodium (Na) and potassium (K) layers registered on 24 June 2023 by the dual-beam Na/K LIDAR system operating over the low-latitude sector of São José dos Campos - Brazil (23.1°S; 45.9°W), a region under the influence of the South Atlantic Magnetic Anomaly (SAMA). In this event, these peculiar metal clouds presented a strong and quick intensification with a vertical extension of ∼4 km and a duration of only a few minutes. At the same time, evidence of Energetic Particle Precipitation (EPP) was observed in the low-latitude ionosphere. Such a record of the metal layers is rare and presents unique characteristics since it seems to be the Na and K cloud that precedes the C-structures. This suggests that, unlike previous observations over the Brazilian sector, the slightly deformed clouds of metal are formed much near the line of the sight of the LIDAR, which makes this event quite rare and intriguing to study.